The Early Galician Immigration in Buenos Aires: Conditions and Characteristics of its Socio-occupational Insertion - de Cristóforis, Nadia Andrea (Madrygal. Revista de Estudios Gallegos, 2017)
The migrations of Galicians to Buenos Aires increased at the end of the colonial period. This phenomenon was stimulated by the increase in the emigration rate in the Spanish Northwest and the attraction exerted by the colonial capital. In this paper we will focus on the processes of socio-occupational insertion of the Galicians in the late colonial Buenos Aires. To do so, we will base mainly on nominative documentation (the registers of inhabitants of 1806-1807 and 1810 or the matrimonial proceedings) which will be complemented by qualitative sources (wills of Galician immigrants or several records of the Archivo General de la Nación of Argentina). First, we will analyze the characteristics of the Galicians’ occupational structure. Secondly, we will focus on business activities undertaken by these immigrants. We will explain in what they consisted and what were the ways of entry to the commercial exercise. We believe that the traits of Río de la Plata trade, offering accessible ways of entry to newcomers, and the assistance provided by ethnic and family networks, allowed Galicians to insert in circuits of exchanges and remain in them with variable success. Also, the significant degree of insertion in the commercial field could have impacted on occupational niches that were configured in the period of Galicians’ mass immigration.
Keywords: Immigrants; Galicians; City of Buenos Aires; Socio-occupational Insertion.